PENGARUH LITERASI KEUANGAN, PERSEPSI KEMUDAHAN, PERSEPSI MANFAAT TERHADAP MINAT BERINVESTASI PADA REKSA DANA SYARIAH (STUDI PADA GENERASI MILENIAL INDONESIA) - Ratmoro, Shindu Dwitama (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Indonesia is a country with the largest Muslim population in the world. It makes Indonesia have a great potential to develop their Islamic finance, especially in the field of Islamic investment. But Indonesia has not been able to maximize its potential. One of the sharia investments instruments that shows positive developments in Indonesia is sharia mutual funds. This study aims to examine factors that affect the intention to invest in Islamic mutual funds on Indonesian millennial generation. The method used in this research is quantitative with logistic regression analysis. The results of this study indicate that partially and simultaneously the variables of financial literacy, perceived ease of use, and perceived benefit have a significant and positive effect on the intention to invest in Islamic mutual funds. These results are in accordance with the hypothesis formulated in this study